Intracoronary Autologous Cardiac Progenitor Cell Transfer in Patients With Hypoplastic Left Heart Syndrome. Issue 4 (13th February 2015) - Ishigami, Shuta; Ohtsuki, Shinichi; Tarui, Suguru; Ousaka, Daiki; Eitoku, Takahiro; Kondo, Maiko; Okuyama, Michihiro; Kobayashi, Junko; Baba, Kenji; Arai, Sadahiko; Kawabata, Takuya; Yoshizumi, Ko; et al.
<x xml:space="preserve">Abstract</x> Rationale: Hypoplastic left heart syndrome (HLHS) remains a lethal congenital cardiac defect. Recent studies have suggested that intracoronary administration of autologous cardiosphere-derived cells (CDCs) may improve ventricular function. Objective: The aim of this study was to test whether intracoronary delivery of CDCs is feasible and safe in patients with hypoplastic left heart syndrome. Methods and Results: Between January 5, 2011, and January 16, 2012, 14 patients (1.8±1.5 years) were prospectively assigned to receive intracoronary infusion of autologous CDCs 33.4±8.1 days after staged procedures (n=7), followed by 7 controls with standard palliation alone. The primary end point was to assess the safety, and the secondary end point included the preliminary efficacy to verify the right ventricular ejection fraction improvements between baseline and 3 months. Manufacturing and intracoronary delivery of CDCs were feasible, and no serious adverse events were reported within the 18-month follow-up. Patients treated with CDCs showed right ventricular ejection fraction improvement from baseline to 3-month follow-up (46.9%±4.6% to 52.1%±2.4%; P=0.008). Compared with controls at 18 months, cardiac MRI analysis of CDC-treated patients showed a higher right ventricular ejection fraction (31.5%±6.8% versus 40.4%±7.6%; P=0.049), improved somatic growth (P=0.0005), reduced heart failure status (P=0.003), and lower incidence of coil occlusion for collaterals (P=0.007). Conclusions: Intracoronary infusion of autologous CDCs seems to be feasible and safe in children with hypoplastic left heart syndrome after staged surgery. Large phase 2 trials are warranted to examine the potential effects of cardiac function improvements and the long-term benefits of clinical outcomes. Clinical Trial Registration: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01273857.